Monoatom-substituted polyacid cluster-based two-dimensional nanosheet as well as preparation method and catalyst thereof
By introducing rare earth and transition metal single atom substitution sites into polyacid clusters and controlling their interactions, the ultra-thin polyacid cluster nanosheet superstructure was successfully synthesized, which was used for efficient catalysis and recovery catalysts, and the clusters were solved The limitations of assembly superstructure synthesis have achieved environmentally friendly and economical catalytic effects.
Patent Information
- Application Number
- CN202411623023.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The isotropic surface of the cluster limits the synthesis of cluster assembled superstructures with programmable structures and custom properties.
By introducing rare earth and/or transition metal single atom substitution sites, programmable interactions between and within the polyacid cluster building blocks were controlled, and ultrathin polyacid cluster nanosheet superstructure was successfully obtained. The nanosheets are connected by intermolecular forces and/or coordination bonds, and the surface ligands are protected by electrostatic adsorption.
It realizes efficient photocatalysis and olefin epoxidation catalysis, the catalyst can be recycled and reused, does not contain heavy metals, is cheap and is environmentally friendly.
Smart Images

Figure CN119455997A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to single-atom substituted polyacid cluster-based two-dimensional nanosheets and preparation methods and catalysts thereof. Background Art
[0002] Clusters with atomically precise structures are unique aggregate states of matter between atoms and nanocrystals. Due to the similarity of their chemical and electronic properties, clusters can serve as “superatomic” primitives for building cluster-based assemblies. However, apart from atomic / molecular building blocks with well-defined connection patterns, the isotropic surfaces of clusters may largely limit the synthesis of cluster-assembled superstructures with programmable structures and customized properties. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a low-cost, heavy metal-free or recyclable single-atom-substituted polyacid cluster-based two-dimensional nanosheet and a preparation method and catalyst thereof.
[0004] In a first aspect of the present application, a two-dimensional nanosheet based on a polyacid cluster substituted with a single atom is provided. According to an embodiment of the present application, the two-dimensional nanosheet based on a polyacid cluster comprises: a plurality of Keggin-type polyacid clusters [PW 11 MO 39 ], adjacent to the Keggin-type polyacid cluster [PW 11 MO 39 ] are connected by intermolecular forces and / or coordination bonds; surface ligands, the surface ligands are electrostatically adsorbed on the Keggin-type polyacid clusters [PW 11 MO 39 ] surface; wherein M includes at least one of rare earth elements and transition metal elements. In other words, the polyacid cluster-based two-dimensional nanosheet is an ordered assembly of clusters with surface-coated cationic surface ligands. The present application successfully obtains an ultrathin polyacid cluster nanosheet superstructure by introducing rare earth and / or transition metal single-atom substitution sites and controlling the programmable interactions between and within the polyacid cluster building blocks. The superstructure can be used as a catalyst for photocatalysis and olefin epoxidation reactions, has high catalytic efficiency, can be recycled and reused, does not contain heavy metals, is low in price, and is environmentally friendly.
[0005] According to an embodiment of the present application, the polyacid cluster-based two-dimensional nanosheet is in the shape of a ribbon, and the adjacent Keggin-type polyacid clusters [PW 11 MO 39] are connected by coordination bonds. Specifically, metal M can form coordination bonds with O, and then multiple Keggin-type polyacid clusters are connected together by MO bonds. As an example, multiple Keggin-type polyacid clusters can be interconnected and spread out to form a two-dimensional nanosheet. The two-dimensional nanosheet can be effectively used as a catalyst in reactions such as photocatalysis and olefin epoxidation catalysis, and has high catalytic activity.
[0006] In some other embodiments, the polyacid cluster-based two-dimensional nanosheets are square in shape, and adjacent Keggin-type polyacid clusters [PW 11 MO 39 ] are connected by intermolecular forces. In the nanosheet, the polyacid clusters are basically in a single-layer flat state, which can be effectively used as catalysts in reactions such as photocatalysis and olefin epoxidation catalysis, and has high catalytic activity.
[0007] According to an embodiment of the present application, the Keggin-type polyacid cluster [PW 11 MO 39 ] has a size of 0.7 to 0.9 nm.
[0008] According to the embodiment of the present application, the thickness of the polyacid cluster-based two-dimensional nanosheet is 2.5 to 4 nm. Within the above thickness range, the polyacid cluster-based two-dimensional nanosheet can achieve a single-layer spreading state, and when used for catalysis, the effective contact area is larger and higher catalytic activity can be achieved.
[0009] According to an embodiment of the present application, the Keggin-type polyacid cluster [PW 11 MO 39 ] and the surface ligand has a mass ratio / molar ratio of 100:20-30.
[0010] According to an embodiment of the present application, the M element includes at least one of Y, Pr, Nd, Gd, Dy, Er, Fe, Mn, and Ni.
[0011] According to an embodiment of the present application, the surface ligand includes at least one selected from hexadecyltrimethylammonium bromide, tetrabutylammonium bromide, and oleylamine. The surface ligand can be effectively adsorbed on the surface of the polyacid clusters through electrostatic action to protect the structure of the polyacid clusters.
[0012] In a second aspect of the present application, a method for preparing the above-mentioned polyacid cluster-based two-dimensional nanosheet is provided. According to an embodiment of the present application, the method comprises: an inorganic salt containing an M element, a Keggin-type polyacid cluster H3PW 12 O 40xH2O is mixed with water to obtain an aqueous solution; the surface ligand is mixed with an organic solvent to obtain an organic solution; the aqueous solution and the organic solution are mixed and reacted to obtain the single-atom substituted polyacid cluster-based two-dimensional nanosheet.
[0013] According to an embodiment of the present application, the inorganic salt containing the M element includes at least one of a nitrate of the M element and a chloride of the M element.
[0014] According to the embodiments of the present application, inorganic salts containing M elements, Keggin-type polyacid clusters H3PW 12 O 40 · xH2O can be mixed in a molar ratio of 140 to 160:40 to 60. Thus, two-dimensional nanosheets can be assembled in an appropriate ratio.
[0015] According to an embodiment of the present application, the surface ligand includes at least one selected from hexadecyltrimethylammonium bromide, tetrabutylammonium bromide, and oleylamine. The surface ligand can be effectively adsorbed on the surface of the polyacid clusters through electrostatic action to protect the structure of the polyacid clusters.
[0016] According to an embodiment of the present application, the organic solvent includes at least one of chloroform, toluene and octadecene, thereby being able to dissolve the surface ligands well and facilitating subsequent reactions.
[0017] In some embodiments, the temperature of the reaction of the aqueous solution and the organic solution is 50-70°C, and the reaction time is 2-5 hours. Within the above temperature and time ranges, the polyacid clusters can form a structure connected by coordination bonds, and then assemble to form two-dimensional nanosheets.
[0018] In some embodiments, the temperature of the reaction of the aqueous solution and the organic solution is 100-150°C, and the reaction time is 2-5 hours. Within the above temperature and time ranges, the polyacid clusters can form a structure connected by intermolecular forces, and then assemble to form two-dimensional nanosheets.
[0019] The third aspect of the present application provides a catalyst. According to an embodiment of the present application, the catalyst includes the polyacid cluster-based two-dimensional nanosheets described above or the polyacid cluster-based two-dimensional nanosheets prepared by the method described above. The catalyst can be effectively used in reactions such as photocatalysis and olefin epoxidation catalysis, and has high catalytic activity. The polyacid clusters and surface ligands in the polyacid cluster-based two-dimensional nanosheet superstructure are inexpensive and do not contain heavy metals, and the catalyst after the catalytic reaction can be recovered by centrifugation to obtain a pure product for reuse. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a transmission electron microscope photograph of the single-atom substituted polyacid cluster-based two-dimensional nanosheet prepared in Example 1 of the present application.
[0021] Figure 2 This is a transmission electron micrograph of the single-atom-substituted polyacid cluster-based two-dimensional nanosheet prepared in Example 7 of the present application.
[0022] Figure 3 This is a graph showing the test results of the yield and conversion frequency of olefin epoxidation reaction using single-atom substituted polyacid cluster-based two-dimensional nanosheets prepared in Examples 1 and 7 of the present application. DETAILED DESCRIPTION
[0023] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0024] This application is based on the inventor's discovery and understanding of the following facts and problems:
[0025] In order to overcome the limitation of the isotropic surface of clusters on the synthesis of cluster assembly superstructures, the inventors proposed that single metal atoms can be introduced into specific positions of polyacid clusters, which may serve as anisotropic interaction sites for directional coordination bonds in modular synthesis; at the same time, polyacid clusters with highly negatively charged surfaces can be easily modified by cationic surfactants of different alkyl chain lengths, so adjustable non-covalent interactions can be used to guide the programmable regulation of coordination sites, quantity and orientation. Based on these anisotropic clusters, the inventors successfully achieved the synthesis of single-layer two-dimensional nanosheet superstructures.
[0026] In view of this, in the first aspect of the present application, a two-dimensional nanosheet based on a polyacid cluster substituted with a single atom is provided. According to an embodiment of the present application, the polyacid cluster-based two-dimensional nanosheet comprises: a plurality of Keggin-type polyacid clusters [PW 11 MO 39 ], adjacent to the Keggin-type polyacid cluster [PW 11 MO 39 ] are connected by intermolecular forces and / or coordination bonds; surface ligands, the surface ligands are electrostatically adsorbed on the Keggin-type polyacid clusters [PW 11 MO 39] surface; wherein M includes at least one of rare earth elements and transition metal elements. In other words, the polyacid cluster-based two-dimensional nanosheet is an ordered assembly of clusters with surface-coated cationic surface ligands. The present application successfully obtains an ultra-thin polyacid cluster nanosheet superstructure by introducing rare earth and / or transition metal single-atom substitution sites and controlling the programmable interactions between and within the polyacid cluster building blocks. The superstructure can be used as a catalyst in photocatalysis and olefin epoxidation catalytic reactions, has high catalytic efficiency, can be recycled and reused, does not contain heavy metals, is low in price, and is environmentally friendly.
[0027] According to the embodiments of the present application, the shape of the polyacid cluster-based two-dimensional nanosheet is not particularly limited. In some embodiments, the polyacid cluster-based two-dimensional nanosheet is in the shape of a ribbon, and adjacent Keggin-type polyacid clusters [PW 11 MO 39 ] are connected by coordination bonds. Specifically, metal M can form coordination bonds with O, and then multiple Keggin-type polyacid clusters are connected together by MO bonds. As an example, multiple Keggin-type polyacid clusters can be interconnected and spread out to form a two-dimensional nanosheet. The two-dimensional nanosheet can be effectively used in reactions such as photocatalysis and olefin epoxidation catalysis, and has high catalytic activity.
[0028] In some other embodiments, the polyacid cluster-based two-dimensional nanosheets are square in shape, and adjacent Keggin-type polyacid clusters [PW 11 MO 39 ] are connected by intermolecular forces. In the nanosheet, the polyacid clusters are basically in a single-layer flat state, which can be effectively used in reactions such as photocatalysis and olefin epoxidation catalysis, and has high catalytic activity.
[0029] It can be understood that the "square" herein includes square, rectangle, approximately square, approximately rectangular shapes. The intermolecular force refers to the van der Waals force, which refers to the relatively weak interaction between molecules, including but not limited to hydrogen bonding, dipole-dipole interaction, London dispersion force, etc.
[0030] According to an embodiment of the present application, the Keggin-type polyacid cluster [PW 11 MO 39 ] has a size of 0.7-0.9 nm, specifically 0.7 nm, 0.72 nm, 0.74 nm, 0.76 nm, 0.78 nm, 0.8 nm, 0.82 nm, 0.84 nm, 0.86 nm, 0.88 nm, 0.9 nm, etc. Within the above size range, the cluster can be used as an atomically precise assembly primitive model to explore the assembly behavior of sub-nanometer materials.
[0031] In this paper, Keggin-type polyacid clusters [PW11 MO 39 ] refers to the diameter of a single cluster, which can be specifically detected by atomic force microscopy.
[0032] According to the embodiments of the present application, the thickness of the polyacid cluster-based two-dimensional nanosheet is 2.5 to 4 nm, specifically 2.5 nm, 2.8 nm, 3 nm, 3.2 nm, 3.5 nm, 3.8 nm, 4 nm, etc. Within the above thickness range, the polyacid cluster-based can achieve a single-layer spreading state, and when used for catalysis, the effective contact area is larger, and a higher catalytic activity can be achieved.
[0033] In this paper, the thickness of polyacid cluster-based two-dimensional nanosheets can be detected by atomic force microscopy.
[0034] According to an embodiment of the present application, the Keggin-type polyacid cluster [PW 11 MO 39 The mass ratio of the surface ligand to the surface ligand is 100:20-30, specifically 100:20, 100:21, 100:22, 100:23, 100:24, 100:25, 100:26, 100:27, 100:28, 100:29, 100:30, etc. Thus, a better composition can be formed into a two-dimensional nanosheet.
[0035] According to an embodiment of the present application, the M element includes at least one of Y, Pr, Nd, Gd, Dy, Er, Fe, Mn, Ni, etc.
[0036] According to an embodiment of the present application, the surface ligand includes at least one selected from hexadecyltrimethylammonium bromide, tetrabutylammonium bromide, and oleylamine. The surface ligand can be effectively adsorbed on the surface of the polyacid clusters through electrostatic action to protect the structure of the polyacid clusters.
[0037] In a second aspect of the present application, a method for preparing the above-mentioned polyacid cluster-based two-dimensional nanosheet is provided. According to an embodiment of the present application, the method comprises:
[0038] S1: Inorganic salts containing M elements and Keggin-type polyacid clusters H3PW 12 O 40 xH2O is mixed with water to obtain an aqueous solution, where x is an uncertain value.
[0039] According to an embodiment of the present application, the inorganic salt containing the element M includes at least one of a nitrate of the element M and a chloride of the element M. As an example, the inorganic salt containing the element M may be yttrium nitrate, praseodymium nitrate, neodymium nitrate, gadolinium nitrate, dysprosium nitrate, erbium chloride, iron nitrate, manganese nitrate, nickel nitrate, and the like.
[0040] According to the embodiments of the present application, inorganic salts containing M elements, Keggin-type polyacid clusters H3PW 12 O 40 xH2O can be mixed in a molar ratio of 140-160:40-60 (specifically, 140:40, 145:40, 150:40, 155:40, 160:40, 140:45, 140:50, 140:55, 140:60, etc.), thereby assembling two-dimensional nanosheets in an appropriate ratio.
[0041] It should be noted that H3PW 12 O 40 In xH2O, x refers to the amount of crystal water, which can be 0 or not. 12 O 40 xH2O can be purchased directly. The value of x is not clearly marked in the commercially available product. Therefore, it is not restricted in this article and the commercially available product can be used.
[0042] S2: Mixing the surface ligand with an organic solvent to obtain an organic phase solution.
[0043] According to an embodiment of the present application, the surface ligand includes at least one selected from hexadecyltrimethylammonium bromide, tetrabutylammonium bromide, and oleylamine. The surface ligand can be effectively adsorbed on the surface of the polyacid clusters through electrostatic action to protect the structure of the polyacid clusters.
[0044] According to an embodiment of the present application, the organic solvent includes at least one of chloroform, toluene and octadecene, thereby being able to dissolve the surface ligands well and facilitating subsequent reactions.
[0045] S3: mixing and reacting the aqueous phase solution and the organic phase solution to obtain the single-atom substituted polyacid cluster-based two-dimensional nanosheet.
[0046] In this step, after the aqueous phase solution and the organic phase solution are mixed, phase separation occurs, and the inorganic salt containing the M element and the Keggin-type polyacid cluster H3PW in the aqueous phase solution are separated. 12 O 40 xH2O reacts with the surface ligands in the organic phase solution at the interface to generate a single layer of polyacid cluster-based two-dimensional nanosheets.
[0047] According to the embodiments of the present application, by setting different reaction conditions, the polyacid clusters can be connected by different forces to form two-dimensional nanosheets. In other words, by gradually adjusting the reaction time, reaction temperature and ligand content to balance the interaction, two different phases of two-dimensional nanosheets can be obtained.
[0048] In some embodiments, the temperature of the reaction of the aqueous solution and the organic solution is 50-70°C (specifically, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, etc.), and the reaction time is 2-5h (specifically, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc.). Within the above temperature range and time range, the polyacid clusters can form a structure connected by coordination bonds, and then assemble to form two-dimensional nanosheets.
[0049] In some embodiments, the temperature of the reaction of the aqueous solution and the organic solution is 100-150°C (specifically, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, etc.), and the reaction time is 2-5h (specifically, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc.). Within the above temperature range and time range, the polyacid clusters can form a structure connected by intermolecular forces, and then assemble to form two-dimensional nanosheets.
[0050] It is understood that after the organic phase solution and the aqueous phase dissolution reaction are completed, the solid-liquid mixed system directly obtained may include a step of separating the polyacid cluster-based two-dimensional nanosheets in some embodiments. As an example, the solution obtained after the reaction can be centrifuged and washed to obtain the polyacid cluster-based two-dimensional nanosheets.
[0051] In some embodiments, non-polar and / or weak polar solvents and polar solvent solutions may be used for washing and centrifugation. As examples, the solvents that may be used include, but are not limited to, chloroform, dichloromethane, methane, ethanol, isopropanol, acetone, and methanol.
[0052] The third aspect of the present application provides a catalyst. According to an embodiment of the present application, the catalyst includes the polyacid cluster-based two-dimensional nanosheets described above or the polyacid cluster-based two-dimensional nanosheets prepared by the method described above. The catalyst can be effectively used in reactions such as photocatalysis and olefin epoxidation catalysis, and has high catalytic activity. The polyacid clusters and surface ligands in the polyacid cluster-based two-dimensional nanosheet superstructure are inexpensive and do not contain heavy metals, and the catalyst after the catalytic reaction can be recovered by centrifugation to obtain a pure product for reuse.
[0053] The embodiments of the present application are described in detail below.
[0054] Example 1
[0055] Synthesis of polyacid cluster-based ribbon nanosheets by solvothermal reaction (nanosheet-1, according to the synchrotron radiation test results, the clusters are directly connected by coordination bonds)
[0056] 50 μmol H3PW 12 O40 xH2O (Aladdin, P100467) and 150μmol Nd(NO3)3 were dissolved in 4mL deionized water and stirred for 48h to obtain an aqueous phase. CTAB (7mg) and TBAB (6mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 60℃ and reacting for 3h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product. The transmission electron microscope photo is shown in Figure 1 .
[0057] Example 2
[0058] 50 μmol H3PW 12 O 40 xH2O and 140μmol Er(NO3)3 were dissolved in 4mL deionized water and stirred for 48h. CTAB (7mg) and TBAB (6mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 60℃ and reacting for 3h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0059] Example 3
[0060] 50 μmol H3PW 12 O 40 xH2O and 150μmol Fe(NO3)3 were dissolved in 4mL deionized water and stirred for 48h. CTAB (7mg) and TBAB (6mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 55℃ and reacting for 3h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0061] Example 4
[0062] 50 μmol H3PW 12 O 40 xH2O and 140μmol Dy(NO3)3 were dissolved in 4mL deionized water and stirred for 48h. CTAB (7mg) and TBAB (6mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 60℃ and reacting for 2h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0063] Example 5
[0064] 50 μmol H3PW 12 O 40 xH2O and 150μmol Y(NO3)3 were dissolved in 4mL deionized water and stirred for 48h. CTAB (15mg) was dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 60℃ and reacting for 3h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0065] Example 6
[0066] 50 μmol H3PW 12 O 40 xH2O and 150μmol Mn(NO3)2 were dissolved in 4mL deionized water and stirred for 48h. CTAB (7mg) and TBAB (6mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 60℃ and reacting for 3h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0067] Example 7
[0068] Polyacid cluster-based square nanosheets (nanosheet-2, according to synchrotron radiation test results, the clusters are indirectly connected by intermolecular forces) were synthesized by solvothermal reaction
[0069] 50 μmol H3PW 12 O 40 ·xH2O and 150μmol Nd(NO3)3 were dissolved in 4mL deionized water and stirred for 50h to obtain an aqueous phase. CTAB (9mg) and TBAB (7mg) were dissolved in 8mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 120℃ and reacting for 3h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product. The transmission electron microscope photo is shown in Figure 2 .
[0070] Example 8
[0071] 50 μmol H3PW 12 O 40xH2O and 145μmol Dy(NO3)3 were dissolved in 4mL deionized water and stirred for 48h. CTAB (7mg) and TBAB (6mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 120℃ and reacting for 2h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0072] Example 9
[0073] 50 μmol H3PW 12 O 40 xH2O and 150μmol Ni(NO3)3 were dissolved in 4mL deionized water and stirred for 48h. CTAB (7mg) and TBAB (6mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 110℃ and reacting for 3h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0074] Example 10
[0075] 50 μmol H3PW 12 O 40 xH2O and 140μmol Er(NO3)3 were dissolved in 4mL deionized water and stirred for 48h. CTAB (7mg) and TBAB (6mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 60℃ and reacting for 2h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0076] Embodiment 11
[0077] 50 μmol H3PW 12 O 40 xH2O and 150μmol Y(NO3)3 were dissolved in 4mL deionized water and stirred for 48h. CTAB (7mg), TBAB (6mg) and OAM (2mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 60℃ and reacting for 3h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0078] Example 12
[0079] 50 μmol H3PW12 O 40 xH2O and 150μmol Fe(NO3)3 were dissolved in 4mL deionized water and stirred for 48h. CTAB (7mg) and TBAB (6mg) were dissolved in 6mL chloroform to obtain an organic phase. Then, the organic phase was dripped into the aqueous phase and stirred vigorously for 10-30min. The mixture was then transferred to a 10mL Teflon autoclave. After heating to 120℃ and reacting for 3h, the organic phase was separated, washed with chloroform and centrifuged to obtain a white product.
[0080] Performance testing:
[0081] 1. Polyacid cluster-based two-dimensional nanosheets catalyze olefin epoxidation reaction: Add 350 μmol olefin (cyclooctene), not less than 10 mg of the two-dimensional nanosheet catalyst prepared in the example, and 200 μL of H2O2 to 10 mL of CHCl3. The reaction was continuously magnetically stirred at 25°C. After the reaction, the supernatant after centrifugation was quantitatively dispersed in ethanol and analyzed by GC-MS. The internal standard method (toluene) was used to quantitatively analyze the product yield. The yield and conversion frequency test results are shown in Table 1, and the yield and conversion frequency results of Example 1 and Example 7 are shown in the figure. Figure 3 .
[0082] 2. Stability test: The precipitate obtained by centrifugation in 1 above (i.e., two-dimensional nanosheets) was washed with ethanol, specifically, centrifugation washing, and then the washed precipitate was added with chloroform and cyclooctene, and the catalytic olefin epoxidation reaction in 1 above was repeated for a cycle test. The conversion frequency test results of the 10th catalytic reaction are shown in Table 1.
[0083] 3. Cluster size: The size of the clusters is obtained by testing the actual samples using an atomic force microscope.
[0084] 4. Thickness of two-dimensional nanosheets: The thickness is tested by atomic force microscopy.
[0085] Table 1
[0086]
[0087] It can be seen from the test results in Table 1 above that the two-dimensional nanosheets of the embodiments of the present application can be effectively used to catalyze olefin epoxidation reactions, have high catalytic activity, high product yield, and can be recovered and reused after simple centrifugal washing.
[0088] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0089] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A two-dimensional nanosheet based on a single-atom-substituted polyacid cluster, characterized in that: include: Multiple Keggin-type polyoxometalate clusters [PW 11 MO 39 ], adjacent to the Keggin-type polyacid cluster [PW 11 MO 39 ] are connected by intermolecular forces and / or coordination bonds; The surface ligand is electrostatically adsorbed on the Keggin-type polyacid cluster [PW 11 MO 39 ]surface; Wherein, M includes at least one of rare earth elements and transition metal elements.
2. The polyacid cluster-based two-dimensional nanosheet according to claim 1, characterized in that: The polyacid cluster-based two-dimensional nanosheet is in the shape of a ribbon, and the adjacent Keggin-type polyacid clusters [PW 11 MO 39 ] are connected by coordination bonds.
3. The polyacid cluster-based two-dimensional nanosheet according to claim 1, characterized in that: The shape of the polyacid cluster-based two-dimensional nanosheet is square, and the adjacent Keggin-type polyacid clusters [PW 11 MO 39 ] are connected by intermolecular forces.
4. The polyacid cluster-based two-dimensional nanosheet according to claim 1, characterized in that: Satisfy at least one of the following conditions: The Keggin-type polyacid clusters [PW 11 MO 39 ] has a size of 0.7 to 0.9 nm; The thickness of the polyacid cluster-based two-dimensional nanosheet is 2.5 to 4 nm; The Keggin-type polyacid clusters [PW 11 MO 39 ] and the surface ligand in a mass ratio of 100:20-30; The M includes at least one of Y, Pr, Nd, Gd, Dy, Er, Fe, Mn, and Ni.
5. The polyacid cluster-based two-dimensional nanosheet according to claim 1, characterized in that: The surface ligand includes at least one selected from hexadecyltrimethylammonium bromide, tetrabutylammonium bromide, and oleylamine.
6. A method for preparing the polyacid cluster-based two-dimensional nanosheet according to any one of claims 1 to 5, characterized in that: include: Inorganic salts containing M elements, Keggin-type polyacid clusters H3PW 12 O 40 xH2O is mixed with water to obtain an aqueous solution; mixing the surface ligand with an organic solvent to obtain an organic phase solution; The aqueous phase solution and the organic phase solution are mixed and reacted to obtain the single-atom-substituted polyacid cluster-based two-dimensional nanosheet.
7. The method according to claim 6, characterized in that The temperature of the reaction between the aqueous solution and the organic solution is 50-70° C., and the reaction time is 2-5 hours.
8. The method according to claim 6, characterized in that The temperature of the reaction of the aqueous phase solution and the organic phase solution is 100-150° C., and the reaction time is 2-5 hours.
9. The method according to claim 6, characterized in that Satisfy at least one of the following conditions: The inorganic salt containing element M includes at least one of nitrate of element M and chloride of element M; The organic solvent includes at least one of chloroform, toluene and octadecene; The molar ratio of the Keggin type polyacid cluster to the inorganic salt containing the M element is 40-60:140-160.
10. A catalyst, characterized in that The invention comprises the polyacid cluster-based two-dimensional nanosheet according to any one of claims 1 to 5 or the polyacid cluster-based two-dimensional nanosheet prepared by the method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Z-type bifunctional composite photocatalyst embedded with polyacid clusters and sulfur indium zinc nanosheets as well as preparation method and application of composite photocatalyst
CN114082444A
Monatomic catalyst loaded by polyacid zeolite imidazate framework as well as preparation method and application of monatomic catalyst
CN118403664A